2021
DOI: 10.1109/tbme.2021.3066876
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Robust Radar-Based Localization and Vital Signs Monitoring in Multipath Propagation Environments

Abstract: Over the last two decades, radarbased contactless monitoring of vital signs (heartbeat and respiration rate) has raised increasing interest as an emerging and added value to health care. However, until now, the flaws caused by indoor multipath propagation formed a fundamental hurdle for the adoption of such technology in practical healthcare applications where reliability and robustness are crucial. Multipath reflections, originated from one person, combine with the direct signals and multipaths of other peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 46 publications
0
40
0
1
Order By: Relevance
“…solutions for naturalistic settings (e.g., individual's homes, long-term care, and hospitals). One of the main challenges in such environments is the existence of stationary objects (i.e., clutter), creating multipath or ghosting effects [1]. Multipath occurs when a signal takes two or more paths from the transmitting antenna to the receiving antenna.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…solutions for naturalistic settings (e.g., individual's homes, long-term care, and hospitals). One of the main challenges in such environments is the existence of stationary objects (i.e., clutter), creating multipath or ghosting effects [1]. Multipath occurs when a signal takes two or more paths from the transmitting antenna to the receiving antenna.…”
mentioning
confidence: 99%
“…Multipath occurs when a signal takes two or more paths from the transmitting antenna to the receiving antenna. The number and particular behaviour of the multiple paths depends on the room structure and the presence of objects [1]. The multipath issue is more significant when people walk in the space since moving even a small object in an environment causes changes in multipath reflections [1].…”
mentioning
confidence: 99%
“…In real life situations, however, the effect of multipath propagation must be taken into account. Some studies reported radar-based physiological measurement techniques that work even in a multipath-rich environment [43]- [46]. It is important to improve the accuracy of the proposed method when it is applied to measurement data recorded in a multipath-rich environment.…”
Section: F Performance Of the Proposed Methods For Non-static Peoplementioning
confidence: 99%
“…This because, current approaches aim at directly extracting the Doppler signals from the received radar signals which are the overall results of the sums of reflections due to direct paths (desired information), multipath, and static reflectors (i.e., clutter, furniture, objects, etc), whose Doppler (phase) information combines non-linearly. In this condition, the radar may: (1) fail to determine the right number of subjects in the room; (2) erroneously conclude people being located elsewhere than the actual location; (3) detect a non-existing person (i.e., a radar ghost) or even represent a life-less object as alive (hence, static objects cannot be simply treated as stationary); (4) assign disturbed signals to an individual 42 .…”
Section: Introductionmentioning
confidence: 99%